Association of polymorphisms in TLR2 and TLR4 with asthma risk: An update meta-analysis. Issue 35 (September 2017) - Zhao, Junling; Shang, Huihui; Cao, Xiaopei; Huang, Yali; Fang, Xiaoyu; Zhang, Shengding; Xie, Min; Xie, Jungang; Liu, Xiansheng
Abstract: Background: Several epidemiological studies have focused on the association between polymorphisms in toll-like receptors ( TLRs ) and asthma. However, the results remained inconclusive. Methods: We systematically reviewed the database of PubMed, EMBASE, Web of Science, CNKI, and Google scholar for all related articles on TLR polymorphisms and asthma. We used the software STATA 12.0 to conduct the meta-analysis. The heterogeneity and publication bias were examined, respectively. Results: Eighteen studies consisting of 3538 asthma cases and 4090 controls were selected into the meta-analysis. The pooled odds ratios (ORs) show that rs3804099 was associated with asthma in dominant model (OR = 1.51, 95% CI = 1.17–1.96, P = .002), and rs4986791 was associated with asthma in additive model (OR = 0.81, 95% CI = 0.64–1.02, P = .07) and dominant model (OR = 0.76, 95% CI = 0.60–0.97, P = .025). Conclusion: The combined results show that rs3804099 in TLR2 and rs4986791 in TLR4 were significantly associated with asthma risk. Polymorphisms in TLRs play important roles in asthma. Abstract : Supplemental Digital Content is available in the text